Molecular phylogenetic and morphological analyses of the traditional tribe Coriandreae (Umbelliferae-Apioideae) - Terenteva, Elena I; Valiejo-Roman, Carmen M.; Samigullin, Tahir H.; Pimenov, Michael G.; Tilney, Patricia M. (Phytotaxa, 2015)
All eight genera (Coriandrum, Bifora, Fuernrohria, Schrenkia, Schtschurowskia, Kosopoljanskia, Lipskya and Sclerotiaria) of the tribe Coriandreae (Umbelliferae), delimited on the basis of morphological characters, were studied using molecular systematic methods to check the monophyly of the tribe. Plastid psbA-trnH data contained very little information and were incongruent with nrDNA data. The nrDNA analyses clearly showed that the tribe Coriandreae consists of three separate groups, differing in their sequences of ITS and ETS of nuclear ribosomal DNA. Only Bifora appears to be closely related to Coriandrum, whereas Fuernrohria falls into tribe Careae, and the five remaining taxa, endemic or subendemic to Middle Asia, form a separate clade, informally named the “Schrenkia clade”. The species of Kosopoljanskia do not form a monophyletic clade, being scattered in molecular trees among the Schrenkia species. Kosopoljanskia and Schrenkia are regarded as congeneric. One new species is described and two new nomenclatural combinations are proposed.